2018
DOI: 10.5539/ijps.v10n3p13
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Working Memory Load and Age on the Comprehension of Passive Sentences

Abstract: The ability of older adults to comprehend sentences may decline due to the cognitive changes in working memory. Therefore, an increase in working memory demands during sentence comprehension would result in poorer performance among older adults. To test this hypothesis, the present study explored the effects of age and working memory load on sentence comprehension using a sentence-picture matching task. 35 older adults and 35 younger adults were required to match Mandarin passive sentences (high working memory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…The most decreased performance on the sentence types with the highest computational load (e.g., passive) was significantly predicted by DS, followed by the IR. These results may imply that the underlying cognitive process engaged in the SCT ( Sung, 2015b ) predominantly relies on short-term memory system rather than long-term memory, aligning with prior aging studies that employed sentence-picture matching paradigms ( Schumacher et al, 2015 ; Sung, 2017 ; Liu, 2018 ; Sung et al, 2020 ). In contrast, DR exhibited no significant correlation with performance on passive sentences and did not emerge as a significant predictor.…”
Section: Discussionsupporting
confidence: 82%
“…The most decreased performance on the sentence types with the highest computational load (e.g., passive) was significantly predicted by DS, followed by the IR. These results may imply that the underlying cognitive process engaged in the SCT ( Sung, 2015b ) predominantly relies on short-term memory system rather than long-term memory, aligning with prior aging studies that employed sentence-picture matching paradigms ( Schumacher et al, 2015 ; Sung, 2017 ; Liu, 2018 ; Sung et al, 2020 ). In contrast, DR exhibited no significant correlation with performance on passive sentences and did not emerge as a significant predictor.…”
Section: Discussionsupporting
confidence: 82%
“…Using a sentence-picture matching paradigm, Sung, Yoo, Lee, and Eom (2017) showed a similar pattern on a behavioral level. Indeed, in their study, older adults who exhibited poorer working memory performances had more difficulties processing non-canonical sentences (i.e., sentences in which the word order is uncommon) (see also, Liu, 2018). In an eyetracking study, Huettig and Janse (2016) showed that prediction in language processing was influenced by working memory and processing speed.…”
Section: Cognitive Control and Language Comprehension In Agingmentioning
confidence: 97%